While We Wait: The Foolishness of Scarcity, the "Devalued Other," and Pedagogies of "Becoming": A Socioeconomic Reading of Matthew 25:1-13 - Joynes, Robin (The ecumenical review, 2019)
This article considers how Christian women leaders might, in the absence of global economic equality for women, reframe theological dialogue that affirms the work and worth of the "devalued other" - 21st-century women living in economic insecurity - and to declare that Jesus' eschatological hope is in the feminization of abundance. The article engages the parable of the wise and foolish virgins as a messianic requirement to deconstruct the barriers that keep the devalued other from seeing her full potential and to challenge the foolishness of scarcity that has taken hold of the daughters of privilege. It seeks to engage an African feminist hermeneutic as the primary methodology and to craft an emerging pedagogy of "becoming" that speaks to the cosmic shift to strengthen the agency of women as we await the coming Parousia.